RHETORICAL DISCURSIVE STRATEGIES OF IS POSTS ON FACEBOOK : RHETORICAL DISCURSIVE STRATEGIES OF IS POSTS ON FACEBOOK - Hamid Tarad Lafta , Lect.; . Hanita Hassan, Assistant Professor; Farah Abdul-Jabbar Al-Manaseer, Assi.Prof. Dr (lark, 2022)
This article investigates and identifies the concept of the self – other representations in IS posts on the FACEBOOK wall, the data involved twenty posts to be analyzed qualitatively. The study is conducted through Fairclough’s CDA (1995) approach and Van Dijk (2006) ideological square model. The article concluded that IS uses several discursive techniques to positively represent the group to the public; while they negatively represent the Muslims and non-muslims. IS deployed several rhetoric strategies to legitimatize its arguments, including actor description, authority, categorization, comparison, generalization, hyperbole, and lexicalization.